PENERAPAN MODEL PEMBELAJARAN AIR (AUDITORY, INTELELLECTUALY, REPETITION) DENGAN MEDIA VIDEO DALAM PEMBELAJARAN BANGUN RUANG UNTUK MENGUKUR HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - dianti, Dina wahi; Pandra, Viktor; Prananosa, Ahmad Gawdy (LP4MK STKIP PGRI Lubuklinggau, 2024)
This study aims to determine the learning outcomes of Mathematics students of grade 5 of SD Negeri 57 Lubuklinggau after the implementation of the AIR Learning Model (Auditor, Intellectualy, Reppetition). This research method is experimental, this study uses Pre-test and Post-test. Sampling was taken from the population, the sample of this study was grade V students of SD Negeri 57 Lubuklinggau totaling 23 students with the sampling technique in this study using saturated sampling. The data collection technique used a multiple-choice test. The data analysis technique used the z test. Based on the results of the z test analysis with a significance level of a = 0.05. The results of the study showed that Zcount = 5.23> Ztable = 1.64. The average pre-test value of students was 43.96 and the average post-test value was 78.52. So it can be said that Ha is accepted and Ho is rejected. The results of this study can be concluded that the Mathematics learning outcomes of grade V students of SDN 57 Lubuklinggau after the application of the AIR Learning model (Auditor, Intellectualy, Reppetition) were significantly complete. Keywords: Learning Outcomes, Auditor, Intellectualy, Reppetition